THE ROLE OF RISK-BASED AUDITING IN ENHANCING THE INFORMATIONAL CONTENT OF FINANCIAL REPORTS (World Economics and Finance Bulletin, 2023)
The research aims to enhance the informational content through the use of risk-based auditing, highlighting the audit risks that the auditor is exposed to, the ability of the auditors to treat them, estimating the acceptable total audit risk, implicit risks, control risks, and the risk of detection for the purpose of bringing it to the lowest level of accommodation to enhance the content. The subject of audit risks receives increasing attention from the concerned professional bodies because it has become a realistic matter that threatens the auditor and that the process of identifying and evaluating its degrees helps him to plan and implement the audit process in a more efficient and effective manner, which leads to more logical results to achieve The objective of auditing the financial statements in a way that meets the needs of the users of the financial statements is the risk-based audit using the auditor’s implementation that enhances the informational content of the financial reports. Based on the risks and the implementation of the audit process, the research recommended the need to pay attention to the subject of audit risks by professional bodies and researchers because it has become a reality that threatens the auditor with the need to use the investigation based on risks because it enhances the informational content of the financial reports. The auditor should plan and implement the audit process using risk-based audit because it enables the auditor to avoid implicit audit risks and the risks of control and discovery. Select highly qualified people to carry out the auditor’s process and be technically and academically skilled and work on setting up developmental courses periodically to assist them. To get acquainted with the new developments related to the profession and to inform them of the latest changes that occur first.
Keywords: Auditing risks; Accounting informational continent; financial reports